A retradução d’O Hobbit de J. R. R. Tolkien no Brasil: contexto, texto e paratexto - Vasconcelos Neto, Hélio Parente de (2023)
This dissertation aims to carry out a critical analysis of the retranslation of J. R. R. Tolkien in Brazil. The British author has had a huge influence on modern fantasy literature, especially in North American and European productions, through his works such as The Lord of the Rings (1954-55) and The Hobbit (1937). This is due, among other reasons, to the fact that Tolkien was concerned with creating a secondary world as complex as our real, primary world, with its own geography, history, languages, and cultures. Therefore, in order to make it possible to analyze his retranslations in Brazil, it is necessary to define a corpus. For this research, the corpus will consist of The Hobbit (1937) and its retranslation into Brazilian Portuguese, O Hobbit (2019a) by Lopes, as the base material. To achieve this objective, the Retranslation Hypothesis, attributed to the French philosopher Antoine Berman (2017), is explored. In addition, contemporary contributions to the Bermanian retranslation hypothesis are analyzed, which bring to light socio-historical aspects, the influence of the market on retranslation and the influence of other editorial agents such as reviewers, editors, and censors. These contributions are exemplified here by Albachten and Gürçağlar (2018), Cadera and Walsh (2017), Van Poucke and Gallego (2019) and Paloposki and Koskinen (2004). The paratexts present in this retranslation are also investigated, whether they are paratexts derived from the translated source text or commissioned for this edition of the work. This dissertation uses Genette's paratextual theory, complementing it with the specific theories on the paratext of translations, through the research of Torres (2011), Cardellino (2015) and Gürçağlar (2011). Finally, the theoretical basis of the research is also grounded on studies on the life and work of J. R. R. Tolkien, such as the research carried out by Scull and Hammond (2017), Rateliff (2011) and Carpenter (2018).